(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
This essay examines the origins of the universal human practice of mentoring. It assembles information from various sources and employs content analysis and socio-linguistic and historical approaches to interrogate and evaluate the material from an Afrocentric perspective. The major focus is upon the concept of mentoring in the widest context of the history of humanity, but with particular attention to intersecting narratives of Kemet (ancient Egypt), Homeric Greece, and the impact of Eurocentrism. The results invalidate popular ideas about the origins of mentoring and confirm that this universal human practice is to be found in all human societies, including the oldest ones, a large number of which predated the Greeks. They demonstrate the practice to be widespread and indeed institutionalized in Kemet, which exerted a tremendous influence upon most subsequent societies, including Greece.